PG131 Supporting the creation of a new simulated patient programme 4000 miles away. (10th November 2020) - Hamilton, Carrie; Thame, Anna; Booth, Jane; Garadah, Taysir Said; Riaz, Salman
Abstract : Introduction: The Arabian Gulf University (AGU), Kingdom of Bahrain, wished to expand their simulation department by setting up a simulated patient (SP) programme. As an independent educational simulation company, who provides SPs to many Universities and Healthcare Trusts in the UK, we were able to provide the tools and information to enable this. Initially this was arranged as an on-site two-day workshop, but due to Covid-19 it was delivered as a remote webinar lecture workshop for 34 attendees over two half-days, 4000 miles away. Methods: The ASPiH standards (ASPiH, 2016) for best practice provided a framework for much of the content, which also included simulation methodology, SP resourcing, safe-guarding, along with practical operational advice. Delivered over Zoom by three presenters, it was supported by live simulation with 6 SPs, training videos, presentations, interactive questionnaires and question and answer sessions. Post-workshop follow-up support was provided, including copies of workshop material and educational resources and references. Results: Logistically, the workshop took significant organisation. Given the geographical and language barriers, clear messages were essential. The university provided IT support and enabled the remote platform and attendees to be effectively managed. The range and depth of subject matter had to be carefully balanced. Interaction between attendees and presenters needed to be supervised to enable full participation without overwhelming the presentations. Feedback from participants was hugely positive. The new simulated patient programme is on course to be live from autumn 2020, with the ASPiH standards providing the foundation. Discussion: It would have been helpful to view the educational environment and have in-depth conversations with the faculty before the course, but this was not feasible. Face-to-face support of the development of a simulation programme is ideal, but much assistance can be offered remotely, especially when backed up by follow-on collaboration and resources. When setting up a new SP programme, support from an experienced SP organisation enables best practice to be shared. By sharing, outputs are enhanced (HEE, 2020) and the creation of a SP programme from scratch, accelerated. From concept to completion, with acquisition of knowledge and materials, reduces costs for the organisation developing the initiative. References: Simulation-Based Education in Healthcare. Standards Framework and Guidance. Association for simulated practice in healthcare (ASPiH) standards for simulation-based education. (2016) http://aspih.org.uk/wp-content/uploads/2017/07/standards-framework.pdf Health Education England ( 2020) COVID-19 tool kit for safe simulation in healthcare, guidance and principles of best practice in simulation-based education and traininghttps://www.hee.nhs.uk/sites/default/files/documents/COVID-19%20toolkit%20for%20safe%20simulation.pdf accessed 25/08/2020